Rossella podagrosa Kirkpatrick, 1907—A valid species after all - Göcke, Christian; Janussen, Dorte; Reiswig, Henry M.; Jarrell, Shannon C.; Dayton, Paul K. (Zootaxa, 2015)
In this study we provide evidence that the species Rossella podagrosa Kirkpatrick, 1907, commonly considered a synonym of Rossella racovitzae Topsent, 1901, is truly a valid species. We show that it can be clearly distinguished from other species especially when taking into consideration the in situ habitus of the sponge in combination with the spicules. Furthermore we demonstrate the weaknesses in the so far published synonymy concept for the very complicated genus Rossella Carter, 1872. From this we conclude that the best strategy for further analysis of Rossella and establishment of acceptable synonymies will need to be based on detailed examination of the spicules, the holotypes, and in situ habitus. When possible it will be useful to analyze specimens from all Antarctic oceanographic regions.